Effect of drought and soil heavy metal contamination on three maple species: a case study of Kastamonu University campus in Türkiye - Savacı, Gamze; Ünal, Sabri; Yer Çelik, Esra Nurten; Karadeniz, Mertcan (Springer Science and Business Media LLC, 2023)
This study investigated the effects of heavy metals and drought on tree drying in three maple species located in the Kastamonu Campus in northwestern Türkiye. Soil samples were taken from 0-30 cm depth under maple species, and some soil properties were analyzed. The standardized precipitation evapotranspiration index was calculated for the drought impression using 71 years of climate data. The severe drought has had its effect (1.516) since August 2020. There was an extreme drought in January and February 2021 (-2.032 and -2.076, respectively), and this drought effect lasted until August as a severe drought. Chromium concentration at maple species was almost twice higher than the Maximum Allowable Limit for Türkiye (> 100 mg kg-1). The highest nickel concentration was found under Acer pseudoplatanus (97.25 mg kg-1) and Acer negundo (108.13 mg kg-1). The sampling sites were nonsignificant for copper (p = 0.806), lead (p = 0.916), and zinc (p = 0.866) heavy metals. Phyllosticta minima and Phyllactinia marissallii were detected in maple trees. In conclusion, it is understood that drought and heavy metal accumulation (chromium, nickel) in the soil affect tree drying. Physiological drought was first seen in trees due to the lack of rainfall in 2020. Soils were contaminated with heavy metals, and finally, diseases were seen. These results show that adverse climate events due to global climate change will have a negative impact on the growth and development of maple species, as their severity is expected to increase in the next few years.
Keywords: Chromium; Turkey; Universities; Acer; Droughts; Trees; Soil; Nickel; Metals, Heavy; Humans; Environmental Monitoring; 15. Life on land; 6. Clean water; 13. Climate action